Influência das contagens de células somáticas e dos microrganismos psicrotróficos sobre os parâmetros físico-químicos de qualidade e índice proteolítico em leite UHT - Silva, Renato Roberto (2021)
The purpose of this study was to evaluate the influence of the level of SC and PSI present in ten batches of raw milk, on the quality of milk before and after UHT, processing throughout its shelf life, evaluating the physicochemical quality parameters and indices of proteolysis. Raw milk was evaluated for SC level, total bacteria, PSI, and physicochemical characteristics, subjected to rapid pasteurization, clarification, and standardization of fat, followed by commercial sterilization by direct UHT process, then aseptically filled. UHT milk analyzes were performed on days 0, 30, 60, 90, and 120 of storage. Additionally, the lots were categorized into groups of the medium, intermediate and high SC, further divided into low, medium, and high PSI counts. In tests of statistical significance, (p<0.05), for raw milk, only alcohol stability was superior at lower SC levels. In pasteurized milk, however, there was no influence of CS or PSI on the quality parameters evaluated. When comparing raw and pasteurized milk, a reduction in CS was observed in all samples after pasteurization/clarification. For UHT milk, no significant changes were observed in the results of acidity, fat, total dry extract, viscosity, density, and lactose related to CS or PSI groups. The values of pH, true protein, casein, proteolysis index, and sedimentation showed significant changes during storage. Proteolysis indices were influenced by high CS and PSI groups. Viscosity increased during storage, but with no significant difference between the established groups. It is concluded that CS and PSI presented high values, indicating that the hygienic-sanitary aspects still fall short. The high counts influenced the increase in casein proteolysis, however, they were at levels that did not cause visual or sensory changes that could cause rejection by consumers.